Finansowanie akcji charytatywnej w diecezji katowickiej w czasie wielkiego kryzysu - Hadrych, Zbigniew (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The great economic crisis caused disastrous social consequences, which resulted in significant deterioration of the financial situation of the inhabitants in the Diocese of Katowice. The most important negative consequences of the economic crisis included unemployment rate at about 40%, vast areas of poverty and the threat of demoralization (alcoholism, vagrancy, prostitution, street children). The Catholic Church took some measures to reduce the negative effects of the crisis. It took care of financing some activities, obtaining the support from the faithful (offerings, special donations, contributions from the members of charitable organizations), local government and central institutions, and organizing various charity events (evenings, dances, stage plays). Particular emphasis should be given to dedication of the clergy and the faithful involved in the work of charities. Their contribution greatly surpassed the donations of other inhabitants of the Province of Silesia. Those of the faithful who were the most aware of the situation- the clergy and parishioners- rose to the challenge and assisted people who were in need. Thanks to their work and generosity, the Church could successfully organize large-scale charity events.